Agroforestry Models in India - Focus on Design - Rastogi, Alind; Srinivas, S. (Indian Forester, 1996)
Design is a stratcgic tool for popularising a particular agroforestry model. The creative potential of scientists shall concentrate upon the value engineering, methods of design optimisation, ergonomic considerations, synergic combinations of tree-crop interactions, designs innovation, and development of models, based upon needs, site capacity, economic returns, and above all, the environmental services. The model designs and preferences may be need (Product) specific, economic value specific, site specific, cultural value specific, technology specific and combination specific. The paper discusses the need to incorporate the design specificitics in agroforestry models because of their importance in participatory forest management and regional planning in India.